(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Questions: What plant species grow on Zamkova Hora in Kyiv? Location: Zamkova Hora (Castle Hill, Khoryvytsia, or Kyselivka), 50.46250º N, 30.51150º E, Kyiv, Ukraine. Methods: field observations. This research was conducted in 2024–2025. Herbarium materials were transferred to the National Herbarium of Ukraine (Kyiv, KW). Nomenclature: POWO 2025 (with some exceptions). Results: Zamkova Hora is a historical area of Kyiv. It is a loess-loamy remnant hill with a relatively flat top and steep slopes. According to the decision of the Kyiv City Council No. 254/915 of March 15, 2007, Zamkova Hora is a natural monument. Its area is 5.9 hectares. Various types of economic activities have been carried out on Zamkova Hora for millennia, so the vegetation cover has always been under significant anthropogenic pressure. Since the 2nd century BC, people have lived here almost continuously. Nowadays, approximately 3/4 of Zamkova Hora is covered with forest, less than 1/4 of its area is covered with grass vegetation. Among woody plants (trees and shrubs), the most common are Acer platanoides, Acer negundo, Euonymus europaeus, Sambucus nigra, Lycium barbarum, among lianas – Parthenocissus inserta and Humulus lupulus, among herbaceous plants – Alliaria petiolata, Chelidonium majus, Cichorium intybus, Impatiens parviflora, Lepidium draba, Thinopyrum intermedium, etc. This article presents an annotated list of plant species and hybrids currently occurring on Zamkova Hora in Kyiv. As a nature conservation site (natural monument), Zamkova Hora has important aesthetic, recreational, and environmental significance. Conclusions: On Zamkova Hora in Kyiv, 192 species and hybrids of vascular plants were recorded; the highest number of taxa belongs to the families Asteraceae (26), Poaceae (15), and Rosaceae (15). Of these, 128 species are native and 64 are non-native. The regionally rare species Convallaria majalis occurs on Zamkova Hora.